PENGARUH KEBIJAKAN MAKROPRUDENSIAL TERHADAP RESIKO KREDIT MACET PADA BPR KONVENSIONAL DI INDONESIA - Tesa Uci Yugita; Ali Anis; Alpon Satrianto (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2017)
This research purpose are to the analyse the (1) LTV Policy, (2)Interest rates on Consumption Loans (3) The Capital Adequacy Ratio  in terms of the Non Performing Loans  in BPR convensional  Indonesia. Methods that being used are Ordinary Least Square (OLS), the estimation results show that (1)LTV Policiy has a significant positive  effect the Non Performing Loans in BPR convensional Indonesia (2) Interest rates on consumption loans has a significant positive effect on Non Performing Loans in BPR convensional Indonesia, and(3) The Capital Adequacy Ratio has a significant positiveeffects the Non Performing Loan in BPR convensional Indonesia.